Effects of Pranayama on mental health and physical fitness in healthy University students - Abhishek Anand; Kishor Patwardhan; R N Singh; Hari Hirdya Awasthi (Wolters Kluwer Medknow Publications, 2018)
Background: In Indian Universities, much attention is not given to the mental and physical fitness of the students during routine teaching-learning sessions except in the courses related to physical education, medicine, and yoga. Even general health-related lessons are mostly not included in the curricula of most of the courses. This fact becomes important in the context of increasing prevalence of cardiovascular and metabolic diseases among the younger population. Yogic training happens to be one of the promising and effective methods of training in developing mental and physical fitness. Objective of the Study: The objective of this study was to find out the effect of Pranayama on physical fitness and mental health in University-level healthy students. Method: A total of 108 adult volunteers of University-level healthy students of both gender, aged 17-28 years were included in the study. The selected individuals were divided into two groups, experimental- and control-with (n = 54) individuals in each group. The training period of Anuloma-viloma and Bhastrika Pranayama for experimental group was 12 weeks. Physical fitness parameters and mental health were assessed at the baseline and after completion of 12 weeks of the training intervention. Mental health was tested with a validated Mental Health Inventory Questionnaire. Control groups did not undergo Pranayama training. Results: The experimental group showed significant improvement in most of the physical fitness parameters after 12 weeks of Pranayama practice; however, the control group did not show significant improvement. The positive effect of Pranayama though was observed on mental health parameters in the experimental group, the difference was not statistically significant when compared with the control group. Conclusion: Anuloma-viloma and Bhastrika Pranayama appear to be effective in improving physical health parameters among healthy University students.